Reading behavior towards Utusan Malaysia among students of Public Institutions of Higher Learning (IPTA) in Klang Valley / Norshida Sulaiman - Sulaiman, Norshida (Faculty of Business and Management, 2007)
This research was conducted for the purposed of "Reading Behavior towards Utusan Malaysia among Students of Public Institution of Higher Learning (IPTA) in Klang Valley: An Exploratory Research. The main objective of this research was to determine readers' reading habits, identify the readers' reading purpose, identify the readers' reading attitudes, determine the readers' preference section and to identify readers' buying frequencies towards Utusan Malaysia newspaper. The respondent of this study was students of Public Institutions of Higher Learning (IPTA) in Klang Valley. 50 questionnaires were collected from them. The researcher had used convenience sampling as the sampling technique. The conclusion of this study was the outcome from the survey analysis and findings. Through the research, it shows their reading behaviour toward Utusan Malaysia is positively contributed by the reading habits, purpose, attitudes and preference and also buying frequency.